(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Patients with end stage renal disease (ESRD), frequently present with intractable pruritus. In the recent past, many newer therapies have emerged for its treatment with variable results. We studied the antipruritic efficacy and safety of Montelukast sodium, (a leukotriene receptor antagonist), and compared it with Gabapentin in patients on hemodialysis. Materials and Methods: The study was conducted in the Department of Dermatology, Sharif Medical and Dental College Lahore. It was a Quasi experimental study, 60 patients on hemodialysis, with refractory pruritus were enrolled in each group .Patients were given 10mg of tab Montelukast sodium daily and 300mg of Gabapentin thrice a week for four weeks. Severity of pruritus was assessed using pruritus scoring by Duo. Results: Pruritus severity score reduced with both the treatments ,but Montelukast showed comparatively higher relief in pruritus score as compared to Gabapentin ( p<0.05). Patients on Gabapentin complained of increased sedation. Conclusions: Montelukast is more effective and safe treatment option for the refractory pruritus in patients with hemodialysis as compared to Gabapentin in our population.